Problematising carer identification: A narrative study with older partner's providing end-of-life care - Tessa Morgan; Robbie Duschinsky; Merryn Gott; Stephen Barclay (Elsevier, 2021)
Internationally health and social care policies have increasingly promoted carer selfidentification as the best way to target and support people in caring roles.There has been remarkably little research concerning how people adopt the identity. This paper explores the carer identification practices of older partners providing end-of-life care.A narrative interview study comprising 41 interviews with 20 participants from 17 couples were conducted between in August 2018-August 2019 in the United Kingdom.This paper coins the term carering to denote the co-constructive practices of policy makers, researchers and broader cultural narratives calling forth the carer identity and the unfolding practices of people interacting with the carer identity in relation to their sense of self.Through three narrative case studies, this paper captures the diversity of older partners carering with three categories defined as engaged, ambivalent and disengaged carering.The carer identity was only taken-up when participants felt that the qualities assigned to being a carer, such as experiencing social isolation and providing 24/7 care, reflected their own personal experience. Given that not every older partner wants to, or will, self-identify as a carer, this paper suggests that carer selfidentification should not be the only strategy to identify and support people involved in caring. Qualitative health researchers also need to be reflexive in their use of the carer identity when studying caring-related topics.